Analysis of design criteria for post-disaster schools using prefabricated architecture concepts (ARTEKS : Jurnal Teknik Arsitektur, 2024)
Indonesia's location in the ring of fire and between three continental plates makes it vulnerable to disasters. As a result, school buildings are damaged and require time and resources to be repaired or enhanced. It emphasizes the need for building designs that can be constructed quickly. As a result, the country's educational system is still developing slowly compared to other countries. The study methodology will involve two forms: gathering data and writing it properly. The writing approach will compare and analyze prefabricated variables among selected prior items.  A comparison of data on school buildings constructed after a disaster or prefabricated methods of construction appropriate for application in these types of circumstances is the result of this study. To maintain a balance in the speed of school procurement that can continue as permanent buildings without the need for emergency or temporary schools, the research aims to ascertain the design criteria for post-disaster schools using prefabricated methods and to determine the correlation between speed and comfort.
Keywords: Post-disaster design; Prefabricated architecture; School building